Visual User Interface Design of “Heay.Id” Application Ease of Telemedicine Services and Healthy Food - Rafi Nandana, Rasha; Almanfaluthi, Betha (International Journal of Art, Design, and Metaverse, 2023)
Mobile applications are one of the solutions for people to get healthy food easily, quickly, and practically. The importance of consuming healthy food because the body must have sufficient and balanced nutrition from what food is consumed and it is an option for managing a healthy lifestyle that must be carried out by every community, especially among adolescents to adults so that the body gets enough energy to move. However, nowadays people consume fast food more often because access is easier online compared to access to healthy food. In addition, there is a lack of electronic media such as mobile applications in Indonesia to provide services for nutritional needs, resulting in a lack of information about healthy food. Therefore it is necessary to have media that can facilitate adolescents in an effective and informative way to meet their nutritional needs. The result of this design is a visual user interface for the mobile application ”HEAY.ID” for the convenience of telemedicine and healthy food.